The erosion of cultural essence: translating mythical cultural terms in classical Chinese folk novels - Wei, Mian; Zainal, Zainor Izat; Wong, Lingyann (Bilingual Publishing Group, 2024)
This paper explores the challenges and implications of translating mythical cultural terms from the Chinese classical literary work Strange Tales from a Chinese Studio. Drawing on the theoretical framework of cultural loss and compensation, this study employs a comparative analysis of two selected English translations by Herbert Giles and John Minford to identify and evaluate the compensation methods used and their impact on preserving cultural essence. Utilizing a qualitative descriptive methodology, this research analyzes selected stories featuring mythical beings, focusing on the translation of specific cultural terms and the use of annotations and contextual explanations. The study examines the extent to which cultural subtleties are preserved or lost in translation, evaluating the effectiveness of compensation methods and their implications for readers' cultural understanding. By examining the translators' choices and their influence on the portrayal of mythical beings, the study aims to provide insights into how cultural subtleties are either preserved or eroded in the translation process. Key findings indicate that while some translations strive to maintain the original cultural essence through careful annotation and contextualization, others prioritise readability and accessibility, leading to significant cultural loss. The paper concludes with recommendations for translators and scholars to enhance cultural preservation in literary translations and suggests directions for future research. This study contributes to the broader discourse on the translation of classical Chinese literature, highlighting the importance of cultural fidelity in translating mythical beings and the role of translators in shaping cultural understanding and appreciation.